An Uncommon Neurological Complication of Tacrolimus: Foot Drop - Vijay Chander Bukka; M. Niranjan; Pallavi Uppal; Ankit Tiwari; M. Prasanna; Prashant Kumar Dixit; Sujanasree Vandrangi; R. Vishnu Vardhan; Siddharth Herur; Anshul Dudani; G. Swarnalatha (Indian Journal of Transplantation)
The use of tacrolimus (TAC) can induce neurologic complications. We report three cases of unilateral common peroneal nerve palsy presenting as foot drop following renal transplantation. Two patients presented within 1 month of renal transplantation and one more patient presented on the postoperative day 40. All the causes of peripheral neuropathy such as trauma, alcohol intake, drugs causing peripheral neuropathy (antibiotics), diabetes, B1, B6, and B12 deficiencies, autoimmune conditions such as antineutrophil cytoplasmic antibody vasculitis and systemic lupus erythematosus, were excluded by history and relevant serology and imageology. TAC levels were found to be high in all three patients, causality was attributed to TAC by temporal relationship and their clinical recovery after reduction in TAC dose in two patients and changing it to everolimus in one patient.